Inflation, Nominal Interest Rates, and the Variability of Output - Chadha, Bankim (IMF Working Papers; Working Paper ;, 1996)
This paper examines the distribution of output around capacity when money demand is a nonlinear function of the nominal interest rate such that nominal interest rates cannot become negative. When fluctuations in output result primarily from disturbances to the money market, the variance of output is shown to be an increasing function of the trend inflation rate. When they result from disturbances to the goods market, the variance of output is a decreasing function of the trend inflation rate. When both disturbances are significant, there exists, in general, a critical non-zero trend inflation rate that minimizes the variance of output.